PENINGKATAN PENGUASAAN KOSAKATA DENGAN METODE COOPERATIVE LEARNING TIPE MAKE A MATCH PADA SISWA KELAS XI IPA SMA TARUNA MANDIRI PEKANBARU - Ria Setia Ningsih; Zuli Laili Isnaini; Sri Wahyu Widiati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research is about the implementation of “make a match” type in cooperative learning in order to improve the students mastery on vocabulary. This research took place in Senior High School of Taruna Mandiri Pekanbaru. The purpose of this research is to know how the procedures are being implemented and to know the degree of improvement by using “make a match” type in cooperative learning. This research is a Classroom Action Research (CAR). The object of this research is students of grade XI IPA Senior High School of Taruna Mandiri Pekanbaru as many as 27 persons. This research is conducted in three cycles. The design used is the designed introduced by Kemmis & Mc. Taggart which the research flow includes steps such as: 1) planning, 2) acting, 3) observing, 4) reflecting. The data collection techtiques used are observation, field note, test on each cycle and documentation. On the cycle I, the result is 52%, on the cycle II increased into 65,38%, and on the cycle III increased into 76,92%. It can be concluded that the implementation of “make a match” type in cooperative learning can improve the mastery on vocabulary of students grade XI IPA Senior High School of Taruna Mandiri Pekanbaru.Keywords :Cooperative learning, make a match, Classroom Action Research, vocabulary.